Avaliação de competências necessárias para a prática da atenção farmacêutica - Souza, Werlissandra Moreira de (2015)
Objective: To evaluate the necessary skills for the practice of pharmaceutical care. Methods: Focus groups were developed to analyze the perceptions of pharmacy students about their training, focusing on the adequacy for professional practice and to obtain contributions from the experts about the recommended content and skills for the suitable training to the practice of pharmaceutical care. A systematic literature review was conducted to identify studies on the teaching and assessment of pharmaceutical care. The analysis of skills was done using a model known as Objective Structured Clinical Examination (OSCE), consisting of three stations before (OSCE BC) and after (OSCE AC) the students attended to the pharmaceutical care course. Each station involved: simulated patients, examiners and pharmaceuticals (played by students). Students were asked to perform a procedure, such as (1) patient education regarding medication administration technique, (2) the measurement of clinical parameters, and (3) invitation of patients to participate in a pharmaceutical care service. Using a standard checklist, the examiners evaluated the students. Results: The pharmacy students do not feel prepared to make decisions, to solve problems and to deal with the unpredictable behavior of patients. The absence of a Pharmacy School, underutilization of the University Hospital and the lack of contact with real patients were the major causes for disability in their professional training in terms of practical knowledge and skills. Excess of theoretical concepts and the didactic and pedagogical shortcomings of teachers also contributed to hide the practical side of the course. In the systematic review it were identified 25 studies with a predominant focus on the development, review and/or revision of pharmaceutical care courses. Many different teaching methods were described, however, in most of them evaluation methods were not in accordance with the new teaching methods described. The very common methods of assessment were written questionnaires and tests. According to the group of experts, it is necessary that students acquire: knowledge on specific diseases and use of drugs, detection and resolution of drug related problems, assistance documentation and monitoring of patient therapy over time, as well as skills to take responsibility for patient education, communication with other health professionals, all important issues in the clinical practice of pharmacy. The group stressed the need to adopt new teaching methods and evaluation to enable effective learning of students in pharmaceutical care and to determine if the desired learning objectives are met. The most of students obtained low scores in all tasks at OSCE BC stations, revealing their lack of preparation to perform them. The overall performance of students at OSCE AC significantly improved in the most of aspects studied after they attended the Pharmaceutical Care course, except for the invitation to join in a pharmaceutical care service task. Students attained the highest overall scores at the measurement of clinical parameter task. Conclusion: The study revealed that there was an increase of the skills of students to the practice of pharmaceutical care after specific course administered directed to the topic under study.